2022
DOI: 10.1136/bmjopen-2021-060238
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of risk factors for diabetic kidney disease progression: a single-centre and cross-sectional experiment in Shanghai

Abstract: ObjectiveTo identify the risk factors for diabetic kidney disease (DKD) development, especially the difference between patients with different courses.Patients and methods791 patients were considered to be eligible and were enrolled in the cross-sectional study from Shanghai Tongren Hospital Inpatient Department. 36 variables were initially screened by univariate analysis. The risk factors affecting progression of DKD were determined by logistics regression analysis. Subgroups were grouped according to the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…retinal barrier (Liu et al, 2022). Therefore, diabetic patients with high UACR levels should be screened for DR by fundus examination as early as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…retinal barrier (Liu et al, 2022). Therefore, diabetic patients with high UACR levels should be screened for DR by fundus examination as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that UACR levels could not only assess the risk of concurrent DR in patients with type 2 diabetes but also were positively correlated with the prevalence of DR. Both glomerular and retinal vessels of the microcirculation system that share similar physiological features, with hyperglycemia driving the production of glycosylation end products, resulting in functional impairment of the vascular endothelium, enhanced oxidative stress and release of inflammatory mediators, causing disruption of the glomerular filtration membrane barrier and blood retinal barrier ( Liu et al, 2022 ). Therefore, diabetic patients with high UACR levels should be screened for DR by fundus examination as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…19 The progression of diabetic nephropathy is also influenced by factors such as gender, blood pressure, and HbA1c concentration. 20 This study identified a significant difference between male and female subjects. The proportion of male subject with DN are higher than the female proportion.…”
Section: Discussionmentioning
confidence: 82%
“…Feng et al [ 24 ] used an adjusted LR model to investigate CKD prevalence and related risk factors in 38 megacities across China. Liu et al [ 25 ] and Yang et al [ 26 ] performed cross-sectional studies to analyze risk factors for diabetic nephropathy in Shanghai, whereas a community-based, 7-year-long cohort study from Tianjin used LR to examine the association between the high triglyceride waist phenotype and risk of CKD development [ 27 ]. Yan et al [ 28 ] performed LR analysis to assess the correlation between residual cholesterol levels and CKD, and identify other significant risk factors affecting middle-aged and older individuals residing within a city.…”
Section: Discussionmentioning
confidence: 99%